Antiplatelet and Anticoagulant Activity of Isorhamnetin and Its Derivatives Isolated from Sea Buckthorn Berries, Measured in Whole Blood - Anna Stochmal; Agata Rolnik; Bartosz Skalski; Jerzy Zuchowski; Beata Olas (Molecules, 2022)
Blood platelets play a crucial role in hemostasis, the process responsible for keeping blood flowing in the circulatory system. However, unnecessary platelet activation can lead to aggregation at the site of atherosclerotic plaque rapture and the formation of a thrombus, which promotes atherothrombotic diseases. Various dietary components, such as phenolic compounds, are known to demonstrate antiplatelet and anticoagulant properties, and it is possible that these could form an important element in the prophylaxis and therapy of cardiovascular diseases. Our present study examined the biological activity of isorhamnetin (1) and two isorhamnetin derivatives, (2): 3-O-beta-glucoside-7-O-alpha-rhamnoside and (3): 3-O-beta-glucoside-7-O-alpha-(3″′-isovaleryl)-rhamnoside, isolated from the phenolic fraction of sea buckthorn fruit, against human washed blood platelets and human whole blood in vitro. The anti-platelet and anticoagulant potential was determined using (A) flow cytometry, (B) the thrombus-formation analysis system (T-TAS) and (C) colorimetry. The results of the T-TAS test indicate that the AUC10 (Area Under the Curve) of the tested phenolic compounds (compounds 1, 2 and 3; 50 µg/mL) was markedly reduced compared to the control values. Moreover, flavonol demonstrated anti-platelet potential, including anti-adhesive activity, with these effects being more intense in compound 2 than isorhamnetin. Different actions of flavonol on platelet activation may depend on their binding ability to various receptors on blood platelets. However, the mechanism of their anti-platelet potential requires further additional studies, including in vitro and in vivo experiments.